Depletion of the trypanosome pumilio domain protein PUF2 or of some other essential proteins causes transcriptome changes related to coding region length - Jha, Bhaskar Anand; Fadda, Abeer; Mercé, Clémentine; Mugo, Elisha Muchunga; Droll, Dorothea; Clayton, Christine (Eukaryotic cell, 2014)
Pumilio domain RNA-binding proteins are known mainly as posttranscriptional repressors of gene expression that reduce mRNA translation and stability. Trypanosoma brucei has 11 PUF proteins. We show here that PUF2 is in the cytosol, with roughly the same number of molecules per cell as there are mRNAs. Although PUF2 exhibits a low level of in vivo RNA binding, it is not associated with polysomes. PUF2 also decreased reporter mRNA levels in a tethering assay, consistent with a repressive role. Depletion of PUF2 inhibited growth of bloodstream-form trypanosomes, causing selective loss of mRNAs with long open reading frames and increases in mRNAs with shorter open reading frames. Reexamination of published RNASeq data revealed the same trend in cells depleted of some other proteins. We speculate that these length effects could be caused by inhibition of the elongation phase of transcription or by an influence of translation status or polysomal conformation on mRNA decay.
Gesehen am 02.09.2020